Adequação do modelo PMV na avaliação do conforto térmico de crianças do ensino fundamental de Ijuí-RS - Lazzarotto, Nebora (2007)
The search for the knowledge of conditions that provide thermal comfort for children in classroom activities is justified by the background and support for the architectural strategies capable of provide the spaces pertaining to the school with better conditions of habitability and thus to contribute for an educative process of better quality. The demand of thermal comfort is intensified with the need of conservation of energy, productivity in the execution of tasks and quality of the people's life. Laboratory researches developed studies of thermal comfort from the theory of the alternation of heat between the body and the environment, which is predisposed by physical factors, characteristic of the atmosphere, and personal factors, own of the occupants. The evaluation normalization of thermal comfort is based on such formulations and in the field studies recently developed, of which derived in a model applicable to buildings naturally ventilated. Thus, the present work made an effort to verify the applicability of the models normalized for the evaluation of the real conditions of children's thermal comfort in school activity, once the children s organism presents a higher metabolic production of heat tax than in the adult age, being this a personal active variable in the thermal balance. In order to consider this differentiation, a calculation procedure was adopted capable to predict the total metabolic tax starting from the gender, age, weight, height and level of carried out activity. The field researches were accomplished at classroom with five groups in two schools of Ijuí (RS), in a total of 116 students between 8 to 11 years. In the occasion of each measurement, the environmental and personal variables were collected as well as the sensations and the occupants' thermal preferences, in agreement with the suitable methodology in the pertinent norms. Field researches ware made, starting from the collected sensations and of the calculated indexes, descriptive and comparative analyses were accomplished between the gathered data and the comfort indexes calculated according normalized models. The work concluded that the PMV model is applicable for evaluation of thermal comfort considering the researched population, however there is children's tendency to feel lightly warmer than the model esteem. Also the adaptive model was shown satisfactory for evaluation in days of heat, although doesn't appreciate accurately the performance of the garment, which extends the comfort interval for lower temperatures.